2015
DOI: 10.1007/s10461-015-1154-3
|View full text |Cite
|
Sign up to set email alerts
|

Partner Pressure, Victimization History, and Alcohol: Women’s Condom-Decision Abdication Mediated by Mood and Anticipated Negative Partner Reaction

Abstract: Highly intoxicated versus sober women were evaluated using multi-group path analyses to test the hypothesis that sexual victimization history would interact with partner pressure to forgo condom use, resulting in greater condom-decision abdication – letting the man decide whether or not to use a condom. After beverage administration, community women (n=408) projected themselves into a scenario depicting a male partner exerting high or low pressure for unprotected sex. Mood, anticipated negative reactions from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Studies support the hypothesis that persons who believe condoms interfere with pleasure or reduce pleasure, or who rate condom-protected sex as less enjoyable or pleasurable than unprotected sex may be less likely to use condoms in practice, and conversely [72][73][74][75]. This double profile emphasizes the role of cognition or emotion as important factors in the decision process [5,33,[76][77][78]. When making decisions, there exists an imaginary balance between a desire for immediate gratification and delayed gratification.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies support the hypothesis that persons who believe condoms interfere with pleasure or reduce pleasure, or who rate condom-protected sex as less enjoyable or pleasurable than unprotected sex may be less likely to use condoms in practice, and conversely [72][73][74][75]. This double profile emphasizes the role of cognition or emotion as important factors in the decision process [5,33,[76][77][78]. When making decisions, there exists an imaginary balance between a desire for immediate gratification and delayed gratification.…”
Section: Discussionmentioning
confidence: 92%
“…The behavioral change models have emphasized the influence of specific factors as the level of information about HIV, attitudes towards condoms or beliefs related vulnerability to AIDS. But also the influence of other personality dimensions, clinical (for example, fear of negative evaluation, depression, self-esteem or worrying about health) or health-related factors (for example, health locus of control or value in health care) [31][32][33]. Abundant empirical literature suggests that there is some consensus on what variables are most important to explain the condom use behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that at least part of women's inconsistent condom use rates may be due to active resistance of condom use by themselves and their partners. Although women with a sexual assault history may be more likely to acquiesce to men's resistance of condom use due to lower sexual assertiveness and/or fear regarding their partners' reactions to condom use insistence (George et al, 2016;Masters et al, 2014;Stoner et al, 2008), reasons for the association between women's sexual victimization history and their own engagement in condom use resistance are unclear. Additional study is needed to clarify the possible mechanisms underlying these associations, as well as the event-level associations between sexual assault and condom use resistance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, relative to their non-victimized counterparts, women who have experienced sexual victimization are less sexually assertive and more likely to anticipate that their male sex partners will react negatively to condom use insistence, potentially increasing their likelihood of acquiescing to a partner who resists condom use (Stoner et al, 2008;Masters et al, 2014). Although studies have reported that men with a history of sexual aggression perpetration are more likely than non-perpetrators to engage in condom use resistance (Davis & Logan-Greene, 2012;Davis et al, 2016;Purdie, Abbey, & Jacques-Tiura, 2010;Raj et al, 2006), no studies have examined how a history of sexual victimization might relate to women's experiences of condom use resistance from their male partners or their own engagement in condom use resistance. Because women with a sexual victimization history may be especially vulnerable to condom use resistance strategies that involve pressure, manipulation, or coercion (George et al, 2016), research in this area is warranted.…”
mentioning
confidence: 99%
See 1 more Smart Citation